Dynamics of nutrient elements and potentially toxic elements during composting with different organic wastes - Gao, Yiman; Wang, Shuhan; Tan, Wenbing; Xi, Beidou (Frontiers in Sustainable Food Systems, 2023)
The presence and bioavailability of potentially toxic elements in the soil–plant system are major limitations to the application of compost to agricultural soils. In this study, the content changes of nutrients and potentially toxic elements in four organic wastes, namely household waste, sewage sludge, chicken manure, and cow/sheep manure, were analyzed during composting, and the quality of compost products was assessed in view of their impact on the environment. The objective of this study was to determine the evolution of 21 metal elements, including macroelements (Na, K, Ca, Mg), microelements (Fe, Mn, Zn, Cu, Mo, Ni), and potentially toxic elements (Ti, Al, Cr, Cd, Pb, Sb, Li, Co, Be, In, and Sn) during composting. Results showed that the contents of these elements varied considerably between different organic wastes. The contents of some elements (Na, K, Ca, Fe, Ti, Cu) increased substantially after composting due to organic matter decomposition and weight loss, whereas other elements (Mg, Co, Mo, Cr, In) decreased due to water leaching. The compost obtained was characterized by heavy metal contents not exceeding the permissible limits. Principal component analysis (PCA) was carried out to further analyze the relationships between the studied elements in different organic waste and compost products. The PCA results revealed that the macroelements (Na, K, Ca, Mg) contents negatively correlated with PC1, whereas microelements and potentially toxic elements positively correlated with PC1. From the results of the PCA, it was possible to classify the different compost products.